Massive open online course for type 2 diabetes self-management: adapting education in the COVID-19 era. Issue 1 (16th November 2020) - Mackenzie, Scott C; Cumming, Kirsten M; Garrell, David; Brodie, Doogie; Wilson, Lyn; Mehar, Salma; Cunningham, Scott G; Bickerton, Alex; Wake, Deborah J
Abstract : Introduction: Type 2 diabetes self-management education is an essential component of type 2 diabetes care that is traditionally delivered in a face-to-face setting. In response to the recent COVID-19 pandemic, innovative solutions are urgently needed, allowing provision of self-management education that can be delivered in compliance with social distancing policies. Innovations that are self-service and can deliver education efficiently at low cost are particularly appealing to healthcare providers and commissioners. Methods: We aimed to evaluate user uptake, dropout, acceptability, satisfaction, perceived short-term knowledge gain and health benefits/behaviour changes in relation to a free massive open online course (MOOC) in diabetes self-management education, created and delivered during the COVID-19 pandemic. This course, focusing on addressing knowledge and self-management needs for people with type 2 diabetes, made use of online interactive content including expert and patient videos, quizzes, moderated discussion boards and live social media that encouraged personal reflection and goal setting. User expectations and experiences were explored via survey-based methods. Here, we present our experience of developing the course and describe users' experiences. Results: 1991 users registered interest in the course over a 2-week period, with 976 users starting the course and 640 (65.6%) users completing the course in full. Users engaged well, finding the course educational, user-friendly and motivating, demonstrating high completion rates and user satisfaction. A statistically significant (p<0.001) increase in self-reported self-management ability and health knowledge was observed among participants with type 2 diabetes. Discussion: MOOCs in type 2 diabetes self-management education have great potential for delivering education efficiently at scale and low cost. Although engagement can be limited by digital literacy, benefits include flexible and remote access to up-to-date, evidence-based education delivered by a multidisciplinary team of healthcare professionals.